Manajemen Penanganan Sapi Mastitis di Unit Pelaksana Teknis Dinas Balai Pengembangan Bibit Pakan Ternak dan Diagnostik Kehewanan Yogyakarta - OKTAWAN, Adhit Dwi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this study is to know cage management in UPTD BPBPTDK of Agricultural Department of Yogyakarta consist of cage construction, sanitation, utility and equipment, waste and health of milch cow. This study is based on measurement and direct observation in the livestock.The method os this study is direct observational, past data review and interview with the responsible person of the livestock. The data taken is about cage disease and all of supporting data. The data taken between January 2010 untill April 2013. There were 16 lactating milch cows, 16 virgin cows, and 11 calfs. From the data, we can conclude that the cage management in the livestock is good enough but still has weaknesses that need to be fixed.